2016
DOI: 10.1200/jco.2016.34.7_suppl.30
|View full text |Cite
|
Sign up to set email alerts
|

The well-being of long-term cancer survivors.

Abstract: 30 Background: While numerous studies have examined the outcomes of individuals recently diagnosed with cancer, less is known about the well-being of long-term (LT) cancer survivors. Methods: Using the Health and Retirement Study (HRS), a nationally representative survey of US residents over age 50, we defined four cohorts: US residents over age 50, individuals recently diagnosed with cancer (≤4 years from diagnosis), LT cancer survivors (>4 years from diagnosis) and individuals with a chronic condition (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Additionally, in accordance with Färkkilä et al, survivors ≥ 5 years post-diagnosis demonstrate higher societal costs than survivors < 5 years post-diagnosis [ 52 ]. The higher spending by long-term survivors might be explained by their comorbidity burden [ 53 ]. A number of studies have suggested an association between the number of comorbidities and costs [ 14 , 54 , 55 ], however, others suggest this association is limited [ 15 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in accordance with Färkkilä et al, survivors ≥ 5 years post-diagnosis demonstrate higher societal costs than survivors < 5 years post-diagnosis [ 52 ]. The higher spending by long-term survivors might be explained by their comorbidity burden [ 53 ]. A number of studies have suggested an association between the number of comorbidities and costs [ 14 , 54 , 55 ], however, others suggest this association is limited [ 15 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was supported by a study of 90 women with breast cancer, the results found that psychological well-being (41). A cohort study conducted on patients more than 4 years suffering from cancer was found to have better welfare than patients who were newly diagnosed with cancer, this welfare included fewer visits to the doctor or hospitalization due to improved health conditions, and the majority of cancer survivors can work again and have a happiness that is far greater than the newly diagnosed group (42). Another study stated that patients with post-traumatic due to cancer found that patients became stronger, appreciated life, and identified new opportunities (43).…”
Section: Based Onmentioning
confidence: 91%
“…It was reported in the USA and Brazil that cancer survivors were happier than the general population after adjustment for age, sex, and other demographic characteristics [58,59]. In contrast, a previous Japanese study with a smaller-sized sample found no significant difference in the prevalence of feeling happiness between working cancer survivors and cancer-free workers in both male and female local government employees [22].…”
Section: Happinessmentioning
confidence: 99%